2021
DOI: 10.3390/plants10071303
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Supplementation Combined with Split Application of Nitrogen and Sulfur Protects Salt-Inhibited Photosynthesis through Optimization of Proline Metabolism and Antioxidant System in Mustard (Brassica juncea L.)

Abstract: In the present study, the potential of ethylene as ethephon (an ethylene source) was investigated individually and in combination with split doses of nitrogen (N) and sulfur (S) soil treatments for removal of the damaging effects of salt stress (100 mM NaCl) in mustard (Brassica juncea L.). Plants were grown with 50 mg N plus 50 mg S kg−1 soil at sowing time and an equivalent dose at 20 days after sowing [N50 + S50]0d and 20d. Ethephon at 200 μL L‒1 was applied to combined split doses of N and S with or withou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 106 publications
0
30
0
Order By: Relevance
“…It has been observed that growth becomes reduced in plants due to damage of PS II and electron transport rates under stress [41]. In B. juncea, the increased concentration of salt significantly impacted net photosynthetic rate, stomatal conductance, intercellular CO 2 , quantum yield of PS II, Rubisco activity, and PNUE [10]. The study of Singh et al [42] showed the response towards variable concentration of salt, which hampered the photosynthetic apparatus and the water splitting efficiency complex.…”
Section: Photosynthetic Functionsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been observed that growth becomes reduced in plants due to damage of PS II and electron transport rates under stress [41]. In B. juncea, the increased concentration of salt significantly impacted net photosynthetic rate, stomatal conductance, intercellular CO 2 , quantum yield of PS II, Rubisco activity, and PNUE [10]. The study of Singh et al [42] showed the response towards variable concentration of salt, which hampered the photosynthetic apparatus and the water splitting efficiency complex.…”
Section: Photosynthetic Functionsmentioning
confidence: 99%
“…Salinity-impact on the germination has been reported in several crop plants including Brassica juncea [10], Oryza sativa [26], and Triticum aestivum [27]. In salinity (EC 12 dS m -1 )exposed B. juncea genotypes, a significant correlation existed between tolerance index and shoot length, dry matter and also salt tolerance efficiency [28].…”
Section: Growth and Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The adaptive reaction of plants to oxidative stress consists in the rise of the activity of antioxidants enzymes [ 8 , 9 , 10 ]. Remarkably, several studies reported the association between antioxidant activity, heat tolerance, and plant hormones [ 3 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%